ATRIUM AS A MEANS OF ADAPTATION HISTORICAL BUILDINGS TO MODERN CONDITIONS - , Е. В. (Municipal economy of cities. Series: «Economy science», 2013)
The problem of preservation of the historical environment in the context of further development of the centers of cities, examines the experience of the use of the atrium as a possible way to solve this problem.